CAMPUR KODE DALAM PROSES BELAJAR-MENGAJAR DI MADRASAH TSANAWIYAH NEGERI SATUI (THE CODE MIXING IN TEACHING AND LEARNING PROCESS AT MADRASAH TSANAWIYAH NEGERI SATUI) - Lilik Yulianti (Universitas Lambung Mangkurat, 2013)
AbstractThe Code Mixing in Teaching and Learning Process at Madrasah Tsanawiyah NegeriSatui. This research aims to get the data and information about the code mixing inlearning study process at Madrasah Tsanawiyah Negeri in Satui. The method used inthis research with quantitative descriptive. Source of data in this research is oral utteranceof student and teacher in learning study process of code mixing form and field notedata of interview about cause of code mixing, function and code mixing in the learningstudy.The instrument used to collect the data was correct reading technique (perceptionor observation) and capable technique (interview),The result of this research was atcode mixing in learning study process at Madrasah Tsanawiyah of Satui conducted bystudent and teacher have same Ianguage background, that is Language of Banjar.Code mixing in the form of mingling morphology code, frase, and clause. Cause factorof code mixing for example equation of language background, habit, environmental,easy going, freshmen. Code mixing function for example watering down to submitquestion, answer, or comments about learning items; guarantying of friendliness; addingbravery to converse.Keywords: code mixing, learning study processAbstrakCampur Kode dalam Proses Belajar-Mengajar di Madrasah Tsanawiyah Negeri Satui.Penelitian ini bertujuan untuk mendapatkan data dan informasi tentang campur kodedalam proses belajar-mengajar di Madrasah Tsanawiyah Negeri Satui. Metode yangdigunakan dalam penelitian ini adalah deskriptif kuantitatif. Sumber data dalampenelitian ini adalah ucapan lisan siswa dan guru dalam proses belajar-mengajartentang bentuk campur kode dan data catatan lapangan dari wawancara tentangpenyebab campur kode, fungsi pencampuran dan campur kode dalam. Instrumen yangdigunakan untuk mengumpulkan data yang benar teknik membaca (persepsi atauobservasi) dan teknik wawancara. Hasil penelitian ini berada di campur kode dalamproses belajar-mengajar di Madrasah Tsanawiyah Satui dilakukan oleh siswa danguru berlatar belakang bahasa yang sama, yaitu Bahasa Banjar. Pencampuran dalambentuk berbaur kode morfologi , frase , dan klausa Code. Faktor penyebab campurkode misalnya persamaan latar belakang bahasa, kebiasaan, lingkungan, easy going,. Fungsi campur kode misalnya mempermudah untuk mengirimkan pertanyaan, jawaban,atau komentar tentang item-item pembelajaran, menjamin keramahan, menambahkeberanian untuk berkomunikasi.Kata-kata kunci: campur kode, proses belajar-mengajar